Experimental investigation of direct diamond laser cladding in combination with high speed camera based process monitoring - Scheitler, Christian Josef; Hugger, F.; Hofmann, K.; Hentschel, Oliver; Bätzler, Tim; Roth, S.; Schmidt, Michael (Journal of Laser Applications, 2016)
Laser cladding is an established coating technology which is established as emerging technology for repair applications and for the fabrication of near net shape geometries. Within the scope of coating, repair and additive manufacturing applications single weld tracks are generated on a metal substrate by a laser beam and simultaneously injected metal powder. For coating applications, such as wear-resistant coatings, single weld tracks are positioned next to each other in order to form a continuous surface layer. Coatings against heavy abrasive wear often contain additional particles like tungsten carbide or diamond particles. However, by embedding wear-resistant particles like tungsten or diamond particles, varying applications can be addressed. For example, the cutting ability of industrial tools can be enhanced by embedding diamonds into a coating. In this paper, a novel approach, the direct embedding of diamonds without using a metal matrix during laser cladding is experimentally investigated. As diamonds are susceptible to heat, varying strategies for thermal energy input in the first place different laser modes of operations (continuous wave and pulsed) are investigated for direct diamond laser cladding. Major objectives of the presented research work are homogeneous diamond distribution on the surface of the sheet metal samples, low number of metal covered diamonds, and minor thermal damage to the embedded diamonds. Based on metallographic analyses, the generated samples are evaluated with respect to the previously stated objectives. During direct diamond laser cladding different phenomena like increasing width of a single weld track during one transit and varying penetration depths can be observed. In order to understand and explain these phenomena, a high speed camera is used for process monitoring. For the detection of these process irregularities, cross sections and the data gathered via process monitoring are analyzed. The results which are presented in this paper allow conclusions to be drawn about the laser diamond interaction mechanisms and about processing parameters for embedding diamonds without a metal matrix.
CRIS-Team Scopus Importer:2023-03-07
Keywords: diamond coating; embedding of diamonds; laser cladding; laser metal deposition; process monitoring with high speed camera